2011
DOI: 10.1159/000330925
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diffusion MRI and Apparent Diffusion Coefficient Measurement in the Diagnosis, Staging and Pathological Classification of Bladder Tumors

Abstract: Objectives: Our aim was to investigate the role of simultaneous apparent diffusion coefficient (ADC) measurement and diffusion-weighted MRI (DWMRI) in the diagnosis and differentiation of bladder masses. Methods: Weexamined 45 patients presenting with hematuria by dynamic and diffusion MRI (at b100, b600, b1000 gradients) and cystoscopy. Thirty healthy volunteers without hematuria were also included in the study. Results from imaging techniques were compared to cystoscopic and histopathologic findings. The ADC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…These assessments neglect the heterogeneous distribution of ADC among voxels of the whole tumour. The study by Daggulli [21] assessed the difference in mean ADC between benign and malignant lesions in 45 bladder patients and did not find statistical significance in mean ADC in this patient population, which is in agreement with the findings in our study. A recent study by Suo [28] applied histogram analysis to differentiate bladder cancer from benign lesions and assess tumour stage and found significant differences in skewness and kurtosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These assessments neglect the heterogeneous distribution of ADC among voxels of the whole tumour. The study by Daggulli [21] assessed the difference in mean ADC between benign and malignant lesions in 45 bladder patients and did not find statistical significance in mean ADC in this patient population, which is in agreement with the findings in our study. A recent study by Suo [28] applied histogram analysis to differentiate bladder cancer from benign lesions and assess tumour stage and found significant differences in skewness and kurtosis.…”
Section: Discussionsupporting
confidence: 93%
“…A number of studies have applied quantitative measurement of ADC in the diagnosis of bladder cancer [2127]. These studies showed that there was correlation of tumour ADC with the histological grade [27], stage [25], and invasive and proliferative potential [24] of the bladder tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ADCs can be used to stage bladder cancer. ADCs are lower in higher T‐stage bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder cancers generally show a hyperintense signal because of their higher cellularity and tissue disorganization [8,9] . Since the first report showing the usefulness of DW-MRI in the detection of bladder cancer in 2007, DW-MRI has been increasingly applied in the management of bladder cancer [10][11][12][13][14] . Abou-El-Ghar et al [15] reported that it had a sensitivity of 98.1% and a specificity of 92.3% in detecting bladder cancers in a prospective study.…”
Section: Introductionmentioning
confidence: 99%